Evolution and human equality - Gould, Stephen Jay.; Insight Video (Cambridge, MA : Insight Video, 1987)
Using paleontology, evolutionary biology, genetics, history of science and social history as his tools, Gould tells the fascinating story of how racial differences have been misunderstood by scientists from pre-Darwinian days to the present to justify oppression, exploitation and persecution. He describes how new genetic research methods confirm the African origins of homo sapiens and the biological equality of the races. He concludes with a plea for students to understand the tremendous social and political power of scientific work, and scientists' responsibility to humankind.
Producer, director, and editor, Paul Rocklin ; executive producer, Bob Katz.
Keywords: Human evolution; Racism